If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(8 + -9x) = 0 (8 * 7 + -9x * 7) = 0 (56 + -63x) = 0 Solving 56 + -63x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + -63x = 0 + -56 Combine like terms: 56 + -56 = 0 0 + -63x = 0 + -56 -63x = 0 + -56 Combine like terms: 0 + -56 = -56 -63x = -56 Divide each side by '-63'. x = 0.8888888889 Simplifying x = 0.8888888889
| 3x+9-5x+7-2x=20 | | 7y+45=y-3 | | -x+21=x+9 | | a-17=48 | | 3b-3=9 | | (4x+8)-(2x+4)=2x | | 2x+5(5x-1)=-113 | | 10(c-7)=-36 | | 7/9-= | | 5y/9=45 | | (4x+6)-(2x+4)=2x | | 9x(x+9x)= | | -4.5n+3= | | 3y+20=14 | | 12s-24=0 | | 2(y+1)-5=-15 | | 4j-36=0 | | 8-41=40 | | 4k-42=-1 | | 6+4r=2(r-4) | | 4h-42=-18 | | -10.1=w+.3 | | 5x-3=2x+26 | | 7w+3w=40 | | 7r^2+91r+280=0 | | 23=13+2a | | 200+2x=4x+400 | | 9b-36=0 | | -7x-14y=14 | | -2(5-3x)-6(2x-4)=x+1 | | -12+4t=0 | | 3(5x+39)=(X+26) |